Odpowiedzi

Najlepsza Odpowiedź!
2009-12-27T21:55:48+01:00
Sn=3n²+5n
S₁ = a₁ = 3 + 5 = 8
a₁ = 8
S₂ = a₁+a₂=a₁+a₁+r
S₂=2a₁+r
S₂=3*4 + 5*2 = 22
22= 2*8 + r
r=6
wzor
an = a₁+(n-1)r
a₁₅ = 8 + (15-1)*6 = 8+ 84= 92
a₁₀₃ = 8 + (103-1)*6= 8 + 612= 620
2009-12-28T00:40:12+01:00
Sn=3n²+5n
czyli
n=1, to S₁=3*1²+5*1=3+5=8
n=2, to S₂ = 3*2² + 5*2 = 12 + 10 = 22
Czyli
a₁=8, a₂=14 ( 8 + 14 = 22)
r = 6
an = a₁ + (n-1)r
wobec czego:
a₁₅ = 8 + (15-1) *6 = 8 + 14*6 = 8+84=92
a₁₀₃ = 8 + (103-1)*6 = 8 + 102*6 = 8 + 612 = 620